Análise observacional da relação entre avaliação isocinética de joelhos e lesões musculares de membros inferiores em atletas profissionais de futebol: estudo retrospectivo - Burigo, Ricardo Lima (2020)
Background: Football injuries affect the health and performance of athletes and have a major economic impact on teams. Among football injuries, muscle injuries are the most common, and hamstrings are among the most affected muscles. Objective: To assess the ability of the isokinetic test to detect risk factors for hamstring injuries in professional soccer players. Methods: Analysis of the isokinetic dynamometer tests of professional soccer athletes' knees, the concentric and eccentric peak values of torque (PT) and concentric muscle working (TM) and power (POT). Descriptive analysis consisted of simple, relative frequency and multivariate regressive analysis of variables. Results: In the multivariate regression analysis, for hamstring injuries, the cutoff point (PC) of 170.83 N of concentric PT (non-dominant) was found, the PC of 130.11 N of concentric flexor POT (non-dominant) ), the CP of 181.82 N of concentric PT of flexors (non-dominant), in the concentric TM variable the CP 236.23 (nondominant). These values can be useful to predict the risk of injury in hamstrings. Na association was found between concentric flexor PT on the dominant side and decreased risk of injury on the dominant side OddsRatio (OR) = 0.980, p = 0.037. It predicts that with each increase in the PT measurement unit, the chance of injury to the dominant side decreases by 2%. The OR value = 0.973 (p = 0.037) means that each increase in the concentric flexor POT unit on the dominant side decreases the risk of injury on the dominant side by 2.7%. Conclusion: OR values provided coherent data to reference protocols for rehabilitation and preventive intervention in soccer athletes. The study identified an important risk factor and cutoff points for the main injury in professional football.